Catatan Sebuah Peristiwa pada Masa Amangkurat I Dari Naskah Merapi-Merbabu * - Agung Kriswanto (Manuskripta, 2016)
Mount Merbabu formerly known as Damalung or Pamrihan was the center for the study of literatures and Hindu-Buddhist, the venue for the tradition of writing and copying manuscripts that are now known as Merapi-Merbabu manuscripts. People living in the area seemingly is not closed to outside information, for example from the area of the palace. This had been indicated by the several manuscripts that recorded the events that had taken place in the palace of Mataram, especially during Amangkurat I. One of them was Gita Sinangsaya. The recording of events was not appeared in the text, but it was contained in the colophon of Gita Sinangsaya. Although it was only a short note, but this information is very important because it was written when the events happened, and especially because this recording events was not mentioned by babad of Javanese literature. This article analyzes the historical aspect on a recording events in Gita Sinangsaya that happened in the 1670s based on other information in babad and the Dutch records. === Gunung Merbabu yang dahulu dikenal dengan nama Damalung atau Pamrihan merupakan pusat studi sastra dan agama Hindu-Budha, tempat berlangsungnya tradisi penulisan dan penyalinan naskah-naskah yang sekarang dikenal dengan naskah Merapi-Merbabu. Komunitas yang tinggal di wilayah tersebut rupanya tidak menutup diri terhadap informasi dari luar, misalnya dari wilayah keraton. Hal ini dibuktikan dengan adanya beberapa naskah yang merekam peristiwa yang terjadi di keraton Mataram, khususnya pada masa Amangkurat I. Salah satunya berjudul Gita Sinangsaya. Rekaman peristiwa tidak terdapat dalam teks, melainkan dalamkolofon teks Gita Sinangsaya. Meskipun hanya merupakan catatan kecil, tetapi informasi ini sangat berarti karena ditulis bersamaan dengan peristiwa terjadi dan terutama karena catatan peristiwa ini tidak banyak disebutkan dalam teks-teks babad di lingkungan sastra Jawa. Artikel ini menganalisa kesejarahan sebuah laporan peristiwa dalam naskah Gita Sinangsaya yang terjadi pada sekitar tahun 1670 M berdasarkan informasi lain dalam babad dan catatan Belanda.